2001
DOI: 10.1097/00005768-200106000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise oxygen consumption and substrate use after resistance exercise in women

Abstract: These data indicate that in young RE trained women, acute RE produces a modest increase in VO2 during a 2-h recovery period and an increase in fat oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
0
25

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 21 publications
9
78
0
25
Order By: Relevance
“…This EE is considered very low when compared to the aforementioned studies, which may have an implication on the significance of the current study. Notwithstanding, some studies have reported more robust data from acute responses measured in young individuals as reported by Singhal et al (2009) Binzen et al (2001), the RES can significantly elevate recovery EE for at least 1 h postexercise and fuel utilization favors fat oxidation. It therefore seems improbable that the energy expended because of EPOC contributed significantly to the attenuation of PPL after RES.…”
Section: Discussionmentioning
confidence: 93%
“…This EE is considered very low when compared to the aforementioned studies, which may have an implication on the significance of the current study. Notwithstanding, some studies have reported more robust data from acute responses measured in young individuals as reported by Singhal et al (2009) Binzen et al (2001), the RES can significantly elevate recovery EE for at least 1 h postexercise and fuel utilization favors fat oxidation. It therefore seems improbable that the energy expended because of EPOC contributed significantly to the attenuation of PPL after RES.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of the studies found in the literature which investigated the cardiopulmonary responses in strength training 5,7,8 aimed at men or protocols different from the one used in the present study 6,21,22 . Bizen et al 23 investigated the metabolic responses of a strength training in female individuals. The training consisted of three sets of tem repetitions, 60 seconds of interval between exercises, nine exercises at 70% 1-RM.…”
Section: Discussionmentioning
confidence: 99%
“…Constata-se, então, que há mais discordância do que consenso entre os estudos disponíveis. Alguns deles sustentam que, mesmo após sessões extenuantes de ECR, o EPOC não seria significativo para um gasto calórico diário importante (15) . Outros, porém, indicam que a TMR pode permanecer aumentada em 20% por até 39 horas (9) .…”
Section: Artigo De Revisãounclassified
“…O critério adotado para estabelecer o dispêndio energético proveniente do ECR também não é padronizado: alguns relatam o gasto calórico total da sessão, que inclui a mensuração do consumo de oxigênio durante o exercício somado ao EPOC (17)(18)(19)(20)(21)(22)(23)(24)(25) , outros apenas mensuram o EPOC (9,14,15,(26)(27)(28) ou nem isso, não considerando o período de recuperação pós-exercício para o cálculo do gasto calórico total da sessão (8,29) . Dentre os métodos de prescrição do treinamento, foram testadas as influências de trabalhos em circuito e em séries consecutivas (16,19,22) , manipulando-se o número de séries (23,24) , a intensidade (16,17,20,26,27) , o intervalo de recuperação entre séries e exercícios (17,19) , a velocidade da contração muscular (14,20,21) e a ordem dos exercícios (15) . Em virtude dessas diferenças, também os resultados dos estudos disponíveis apresentam variações para os EPOCs obtidos: a amplitude de variação da magnitude do EPOC em ECR nos estudos localizados oscilou entre ≈5,5kcal (26) e ≈775kcal (9) , com mediana de 41kcal; a duração do EPOC variou entre 15 min (20) e 48h (14) .…”
Section: Artigo De Revisãounclassified